Hemodialysis stent sub-project 2 : heparin immboilisation on polymer surface - Leow, Jian Hao (2017)
Effective dialysis may be disrupted when dialysis access points fail to function due to problems like stenosis. Stents have been introduced to the stenosed access points of dialysis patients as a form of interventional treatment to salvage these access points. Thus, this extends the lifetime of the dialysis access points and continue to deliver adequate blood flow from these end stage renal disease (ESRD) patients to the dialyzer. Yet, the deployments of stents are also associated with complications like thrombosis. Furthermore, the permanent nature of these existing stents in the market may pose limitations to further interventional treatments. So, many existing blood contacting devices attempt to modify the surface characteristics to achieve bioactive surfaces, particularly to improve the hemocompatibility of the device. Also, bioresorbable polymeric materials can open up the potential of a temporal solution, making way for further intervention that may be needed to salvage the same access point, thereby extending the lifetime of the access point. In this work, Heparin is immobilised on the bioresorbable stent cover material, Poly (L-lactide-co-caprolactone) (PLC), in order to improve the thromboresistance of the novel bioresorbable stent for dysfunctional dialysis access points. Heparin is an anticoagulant that impedes the coagulation cascade by activating antithrombin which is responsible in binding to the clotting factors. In this work, PLC films underwent a two-step chemical treatment consisting of aminolysis and crosslinking step. These treatments involved the crosslinking of the carboxylic groups of the Heparin and the induced amine groups on the PLC surface. Furthermore, the effects of the chemical treatment on mechanical stability of the PLC films were investigated.